Unlabeled multi-target regression with genetic programming - Lopez, Uriel (2022)
Lopez, U., Trujillo, L., Silva, S., Vanneschi, L., & Legrand, P. (2020). Unlabeled multi-target regression with genetic programming. In GECCO 2020: Proceedings of the 2020 Genetic and Evolutionary Computation Conference (pp. 976-984). (GECCO 2020 - Proceedings of the 2020 Genetic and Evolutionary Computation Conference). Association for Computing Machinery. https://doi.org/10.1145/3377930.3389846